The influence of the load frequency on the high cycle fatigue behaviour. (April 2017) - Fargione, Giovanna; Giudice, Fabio; Risitano, Antonino
Highlights: Fatigue tests were performed on material with a high heat release. Influence of frequency on energy-based fatigue characterization has been evaluated. High increments in material temperature can cause alterations of fatigue behaviour. Fatigue test frequency must be adapted to load history and material characteristics. Abstract: The energetic methods to determine the fatigue limit, proposed by various researchers in the last decades, are based on the evidence that fatigue is an energy dissipation process, and most of the dissipated energy is converted into heat, which manifests itself in the form of temperature change. The study of fatigue behaviour through the determination of the heat quantity released during the fatigue tests, and the analysis of the temperature variation of material under fatigue loading, by mean of thermography-based methods, constitutes a well-established approach. Reaching very high temperature in the specimen is a critical aspect of this phenomenon of conversion of the dissipated energy into heat, particularly with regards to materials characterized by high thermal releases, that could be subject to microstructural changing and behaviour decay. This effect can be exalted by the use of ultrasonic fatigue testing systems for the characterization of very high cycle fatigue behaviour of material. To highlight the influence of the fatigue test frequency on the specimen temperature that already occurs at low frequencies, in this paper a study of the thermal behaviour of AISI 304 stressed by fatigue loads in high cycle fatigue testing at different frequency values, based on energetic method to determine the fatigue curve, is presented.